Hippocampal Sclerosis in Frontotemporal Dementia: When Vascular Pathology Meets Neurodegeneration. Issue 4 (26th February 2021) - Sieben, Anne; Van Langenhove, Tim; Vermeiren, Yannick; Gossye, Helena; Praet, Marleen; Vanhauwaert, Dimitri; Cousaert, Céline; Engelborghs, Sebastiaan; Raedt, Robrecht; Boon, Paul; Santens, Patrick; De Deyn, Peter Paul; et al.
Abstract: Hippocampal sclerosis (HS) is a common neuropathological finding and has been associated with advanced age, TDP-43 proteinopathy, and cerebrovascular pathology. We analyzed neuropathological data of an autopsy cohort of early-onset frontotemporal dementia patients. The study aimed to determine whether in this cohort HS was related to TDP-43 proteinopathy and whether additional factors could be identified. We examined the relationship between HS, proteinopathies in frontotemporal cortices and hippocampus, Alzheimer disease, cerebrovascular changes, and age. We confirmed a strong association between HS and hippocampal TDP-43, whereas there was a weaker association between HS and frontotemporal lobar degeneration with TDP-43 pathology (FTLD-TDP). Nearly all of the FTLD-TDP cases had TDP-43 pathology in the hippocampus. HS was present in all FTLD-TDP type D cases, in 50% of the FTLD-TDP A cohort and in 6% of the FTLD-TDP B cohort. Our data also showed a significant association between HS and vascular changes. We reviewed the literature on HS and discuss possible pathophysiological mechanisms between TDP-43 pathology, cerebrovascular disease, and HS. Additionally, we introduced a quantitative neuronal cell count in CA1 to objectify the semiquantitative visual appreciation of HS.